Experimental determination of numerical values of critical parameters in the gatifloxacin process development - Ružič, Miloš (Acta chimica slovenica, 2007)
A practical example of the determination of critical parameters is presented on the example of the gatifloxacin process development
Keywords: gatifloksacin; kristalizacija; kritični parametri